The dynamics of grandfathers: A comparative analysis of Mexican and Spanish society - George Leeson; Marta Ortega-Gaspar; Alejandro klein (Research on Ageing and Social Policy, 2022)
In analysing the importance of the current roles of grandfathers in the family in Spain and Mexico, this study attempts to deepen knowledge of these roles in two different social contexts which share similar cultural roots. In respect of gender and from a cultural and generational perspective, the research aims to shed light on the figure and role of grandfathers, who have long been overshadowed by their spouses – the grandmothers.